Priestly Sanctity by Design in Leviticus 21: Discursive Constructions of Gender, Class, and Impurity - Han,Amelia (2025)
This study demonstrates how Leviticus 21 formulates priestly sanctity through laws that regulate gender, class, and impurity within the Holiness Legislation. By applying a synchronic critical discourse analysis, informed by the distinction between ritual and moral impurity, the analysis explores how legal form produces hierarchical exclusions that reinforce priestly dominance, sanctioned through appeals to divine authority. In addition to sacred anointing, which elevates the priesthood above the laity, the chapter embeds hierarchical norms into the fabric of the community in order to maintain institutional legitimacy. Comparative analysis of key textual witnesses (LXX, DSS, MT, NRSVUE) demonstrates that translation and transmission are shaped by the ideological context of scribes, highlighting the interpretive dynamics involved. These texts exert enduring influence on social imagination within communities that treat biblical morality as ethically normative, and they continue to mediate contemporary debates on justice, power, and human dignity.
Keywords: Leviticus 21; Holiness Legislation; biblical law; priestly sanctity; hierarchy; sexuality; impurity; authority; interpretation